Battlefield : social representations of commercial sex work on transvestite and transsexual females in Brazil = Sobre campos de batallas : representaciones sociales del comercio sexual entre mujeres auto-identificadas como transexuales y travestis brasileñas - Caravaca Morera, Jaime Alonso 1986-
To analyze commercial sex work's social representations among Brazilian women who identify as transvestite or transsexual. Methods: A qualitative study with a descriptive and analytical approach based on the Theoretical Paradigm of Social Representation with a structural approach. The sample group was formed by 100 women who defined themselves as transvestite and transsexual in Santa Catarina, Brazil. The data was gathered from September to December 2016 via a questionnaire using the technique of free association of words, as well as semi-directed interviews. Results: Through both prototypical and content analysis, it was confirmed that the most likely elements that formed the core of the social representation were: violence, drugs, risk, work, sadness, prejudice, and danger. In the objectification/objectivation process of commercial sex work, the image shows a mix between daily activities in the streets - which they consider to be their battlefield - and their own feelings and experiences of vulnerability in other areas of society, starting with families, churches, schools and the like. Conclusions: By experiencing commercial sex work, female transvestite and transsexual individuals reveal how the elements that form the social representation are of paramount importance in the legitimation, legalization, and simplification of their identities.